Suasana Kerja dan Pengaruh Kepemimpinan dalam Konteks Pendidikan Dasar - Mieske Theresia Tulung; Laurens Kaluge (Jurnal Pendidikan dan Kebudayaan, 2012)
This study aimed at discovering the leadership perception in conditioning the working climate at schools. Three objectives of the aim were describing working climate, teachers’ perception on leadership, and the causal relationship between them. The cluster proportionate random sampling obtained 386 teachers from 24 state and private junior-secondary-schools in the city of Manado. Data were collected through questionnaire administration and analyzed using descriptive and inferential methods. Eight leadership constructs and two working climate were proven to be valid and reliable. Using range criteria of 0-4, the averages of working climate were 2.9 and 2.8 for working spirit and creative climate. On the other hand, using the same criteria, the average of the eight leadership sub-scales ranged between 2.55 and 3.19. The regression analyses found that not all of the leadership components were significant factors for developing the school working climate. Disciplining, listening, and supporting were significant factors for teachers’ working spirit. Whereas, the creative climate of teachers was affected significantly by disciplining, listening, supporting, and empowering factors. The results would be of benefit for educational policies and school improvement. ABSTRAK Penelitian ini bertujuan mengungkap suasana kerja di sekolah yang dikondisikan oleh persepsi kepemimpinan. Fokus dari tujuan tersebut, yaitu: gambaran suasana kerja, persepsi para guru, dan hubungan kausal antara keduanya. Metode yang ditempuh bersifat kuantitatif. Sampel sebanyak 386 guru diambil dari 24 SMP Negeri dan Swasta di kota Manado secara acak dengan memperhatikan cluster proportionate. Data dianalisis secara deskriptif serta inferensial. Delapan konstrak kepemimpinan dan dua konstrak suasana kerja terbukti valid dan reliabel. Dengan rentangan 0-4, rerata suasana kerja di sekolah sebesar 2,9 untuk semangat kerja, dan 2,8 untuk suasana kreatif. Juga dengan rentangan yang sama, rerata kedelapan subskala kepemimpinan berkisar 2,55 dan 3,19. Analisis regresi mengungkapkan tidak semua komponen kepemimpinan merupakan faktor signifikan untuk pengembangan suasana kerja di sekolah.Kepemimpinan yang mendisiplinkan, mendengarkan, dan mendukung berpengaruh signifikan terhadap semangat kerja para guru, dan pengembangan suasana kreatif dipengaruhi secara signifikan oleh kepemimpinan yang mendisiplinkan, mendengarkan, mendukung, dan memberdayakan. Temuan ini bermanfaat bagi kebijakan pendidikan dan pengembangan sekolah.